Development of a high-throughput tailored imaging method in zebrafish to understand and treat neuromuscular diseases - Lescouzères, Léa; Bordignon, Benoît; Bomont, Pascale (Frontiers in Molecular Neuroscience, 2022)
The zebrafish (Danio rerio) is a vertebrate species offering multitude advantages for the study of conserved biological systems in human and has considerably enriched our knowledge in developmental biology and physiology. Equally important for medical research, the zebrafish has become a critical tool in the fields of diagnosis, gene discovery, disease modeling and pharmacology-based therapy. Studies of the zebrafish neuromuscular system allowed the deciphering of key molecular pathways, and established it as a model of choice to study motor neuron, neuromuscular junction and muscle diseases.Starting with the similarities of the zebrafish neuromuscular system with human, we review the disease models to focus on the current methodologies employed to study them and outline their caveats. In particular, we put in perspective the necessity to develop standardized and highly resolutive methodologies that are necessary not only to deepen our understanding of fundamental signalling pathways in a healthy tissue, but also of the changes leading to disease phenotype outbreaks, and offer templates for high-content screening strategies. While the development of high-throughput methodologies is underway for motility assays, there is no automatized approach to quantify the key molecular cues of the neuromuscular junction. Here, we provide a novel high-throughput imaging methodology in zebrafish that is standardized, highly resolutive, quantitative and fitted for drug screening. By providing a proof of concept for its robustness in identifying novel molecular players and therapeutic drugs in the giant axonal neuropathy (GAN) disease, we foresee that this new tool will be useful for both fundamental and biomedical research.